2007
DOI: 10.1016/j.addbeh.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-related videos for use in cue-induced craving paradigms

Abstract: Environmental cues (e.g., the sight of a cigarette) have long been recognized as important triggers for craving in smokers. Available imaging technologies (e.g., fMRI) allow investigation of the neural mechanisms for cue-induced craving, but there stands a need for a cue-delivery system compatible with an MRI environment. We developed a standardized set of 24 high-resolution videos, 12 containing cigarette smoking scenes (e.g., lighting up), and 12 containing neutral scenes (e.g., reading a book), each 30 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 44 publications
(55 reference statements)
6
51
3
2
Order By: Relevance
“…The present findings, very much consistent with the adult literature (Field & Duka, 2004;Saladin et al, 2012;Tong et al, 2007), show that adolescent females show stronger increases in craving in response to cues than do males. Although both males and females showed increases in cue-elicited craving, the increase was higher among females.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present findings, very much consistent with the adult literature (Field & Duka, 2004;Saladin et al, 2012;Tong et al, 2007), show that adolescent females show stronger increases in craving in response to cues than do males. Although both males and females showed increases in cue-elicited craving, the increase was higher among females.…”
Section: Discussionsupporting
confidence: 82%
“…Women within this same study also trended (i.e., nonsignificant difference) toward heightened responses to smoking cues. Similar research from others (Colamussi, Bovbjerg, & Erblich, 2007;Field & Duka, 2004;Tong, Bovbjerg, & Erblich, 2007) has demonstrated heightened craving in response to smoking and/or stress cues among women. However, in one study most similar to ours, adult smokers administered a cue-exposure session were tested for the effects of gender, smoker group (regular smokers vs. chippers), and their interaction.…”
Section: Introductionmentioning
confidence: 60%
“…The videos each show male and female actors of a variety of ages and ethnicities smoking cigarettes. These were selected from a set of 12 videos which have previously been shown to effectively induce cue-elicited craving (Tong, Bovbjerg, & Erblich, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have concluded that females report higher craving in response to smoking cues (vs. neutral cues) than males 13,14 while others report equivalent levels of post smoking cue craving across genders. 15,16 Taken together, the extant research on gender effects in cue reactivity suggests that, though females may be more reactive to stress cues than males, the evidence for gender differences in smoking cue reactivity is less consistent.…”
Section: Introductionmentioning
confidence: 99%